THE INFORMATION SYSTEM FOR DECISION MAKING WHEN EVALUATING THE MASTER’S THESIS - KUZMINSKA, OLENA; MOKRIIEV, MAKSYM; MAZORCHUK, MARIIA (Computer systems and information technologies, 2021)
Digital transformation involves utilizing information technologies and digital tools to restructure the business processes and increase their efficiency. During the COVID-19 lockdown, this topic becomes even more relevant. This paper covers the digitalization of such processes as preparing the master’s research work and presenting the results. We modeled a system for supporting decision-making when evaluating master's thesis based on the results of expert assessment and automated text verification for plagiarism following the regulatory documents of a higher education institution and general recommendations for observing academic integrity. This paper suggests system implementation via LMS Moodle, determines the resources for loading the master's thesis and accompanying documents, conducting peer review, organizing consulting undergraduates, and communication per the distribution of the roles. To verify texts for plagiarism, the Unicheck module can be integrated with LMS Moodle. The availability of an educational environment in the universities along with the creation of a single user base will allow for implementing the proposed information system with minimal costs.